2022
DOI: 10.1007/s00701-022-05144-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anaemia and red blood cell transfusion in patients with aneurysmal subarachnoid and intracerebral haemorrhage — a multicentre subanalysis of the German PBM Network Registry

Abstract: Purpose Anaemia is common in patients presenting with aneurysmal subarachnoid (aSAH) and intracerebral haemorrhage (ICH). In surgical patients, anaemia was identified as an idenpendent risk factor for postoperative mortality, prolonged hospital length of stay (LOS) and increased risk of red blood cell (RBC) transfusion. This multicentre cohort observation study describes the incidence and effects of preoperative anaemia in this critical patient collective for a 10-year period. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Microdialysis studies and cohort studies have largely supported, with only few exceptions, the notion that anemia in aSAH patients is associated with brain tissue hypoxia, DCI, and poor clinical outcome (Table). 9,10,33,57–75 This critical Hb level appeared to be between 9 and 11 g/dL. In a recent post hoc analysis of 413 aSAH patients in the Clazosentan to Overcome Neurological Ischemia and Infarction Occurring After Subarachnoid Hemorrhage (CONSCIOUS-1) study, a multivariate regression analysis identified anemia postaneurysm securement to be associated with poor neurological outcome (OR, 1.96; 95% CI, 1.07–3.59; P = .03) and death (OR, 3.50; 95% CI, 1.15–10.62; P = .027).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Microdialysis studies and cohort studies have largely supported, with only few exceptions, the notion that anemia in aSAH patients is associated with brain tissue hypoxia, DCI, and poor clinical outcome (Table). 9,10,33,57–75 This critical Hb level appeared to be between 9 and 11 g/dL. In a recent post hoc analysis of 413 aSAH patients in the Clazosentan to Overcome Neurological Ischemia and Infarction Occurring After Subarachnoid Hemorrhage (CONSCIOUS-1) study, a multivariate regression analysis identified anemia postaneurysm securement to be associated with poor neurological outcome (OR, 1.96; 95% CI, 1.07–3.59; P = .03) and death (OR, 3.50; 95% CI, 1.15–10.62; P = .027).…”
Section: Methodsmentioning
confidence: 98%
“…Observational studies have mostly demonstrated an association between anemia and poor outcomes among ICH patients, though again not without inconsistency in the results (Table). 66,97–104 In a meta-analysis of 7 cohort studies from 2009 to 2016 that included 7328 ICH patients, anemia was associated with increased 30-day mortality (OR, 1.72; 95% CI, 1.37–2.15; P = .02; I 2 = 64%), and increased risk of poor functional outcome at 3 months (OR, 2.29; 95% CI, 1.16–4.51; I 2 = 91%; P < .0001). 105 This considerable heterogeneity should be noted when interpreting the data, as the definition of anemia and measurement of Hb varied significantly between studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, brain hypoxia may also occur even in mild anemia [ 9 , 10 ]. Anemia is an independent risk factor for poor prognosis in neurocritical settings [ 11 ]. Previous studies have shown that in patients with TBI, SAH, and ICH, hemoglobin less than 9 g/dl is associated with tissue hypoxia and poor prognosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia is an independent risk factor for poor prognosis in neurocritical settings [ 11 ]. Previous studies have shown that in patients with TBI, SAH, and ICH, hemoglobin less than 9 g/dl is associated with tissue hypoxia and poor prognosis [ 11 ]. However, RBC transfusion is associated with increased postoperative complications, poor neurological recovery, and mortality in critically ill neurologic patients [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%